New direction toward a more secure America. - Lairsey, Johnny M., Jr. (Fort Leavenworth, KS : US Army Command and General Staff College, 2010)
The security of the United States is an enduring dilemma that if not properly addressed will leave the nation vulnerable to existing and future threats. The attacks of September 11, 2001 were a stark reminder of our vulnerability. Despite the initial and subsequent government responses to secure the country, it is still vulnerable to attack. To prevent further attacks in our country it is necessary for the Department of Defense to lead an effort to build a whole of government approach towards securing the nation. The Department of Defense should clarify its existing doctrine on homeland defense, facilitate the sharing of information and assist in developing a family of unified plans that links the actions of the numerous agencies involved in Homeland Security to the strategic end state of providing a safe, and secure environment for the country. Since 1949, the Department of Defense has been a critical component for the common defense of the country. A review of the history of civil defense reveals the extraordinary efforts the government took to protect and prepare the nation against potential attacks. Unfortunately, those efforts failed to achieve a lasting result. This is due to the ever-changing political environment and were subject to budgetary constraints that eventually changed the face of civil defense to one that focused on natural disaster response versus securing the country. The attacks on 9/11 immediately changed the way in which the country viewed its security. In response to the attacks, the government created several new offices responsible for homeland security, redefined other government agencies missions and passed legislation to support their efforts. Eventually a separate Executive Department encompassing twenty-two government agencies was created to serve as the nexus for all matters relating to the security of the nation. Regardless of the numerous efforts to provide for a more secure country, the nation is still vulnerable and it is necessary for the Department of Defense to use its vast ...